Faktor-Faktor Yang Berhubungan Dengan Kejadian Ketuban Pecah Dini (KPD) Pada Ibu Bersalin - Rosdianah, Rosdianah; S, Irmawati (Madu : Jurnal Kesehatan, 2023)
Premature rupture of membranes is one of the most common complications of pregnancy and childbirth and requires greater attention because the prevalence is quite large and tends to increase. This study aimed to identify the factors associated with the incidence of premature rupture of membranes at Pertiwi Mother and Child Hospital Makassar. The case-control design compares two groups, namely the case and control groups. The case sample in this study amounted to 26 people, so the 1:1 control sample amounted to 26 people. The results of statistical tests showed that there was a relationship between the age factor of the delivery mother and the incidence of premature rupture of membranes (p-value = 0.008); there was no relationship between the number of parity factors and the incidence of premature rupture of membranes (p-value = 0.490), and there was no relationship between the distance of pregnancy to the incidence of premature rupture of membranes (p-value = 0.419). It is expected that midwives in carrying out services will further improve education to pregnant women and families to prevent the occurrence of premature rupture of membranes and can take quick and appropriate action if premature rupture of membranes occurs.